An open nanowindow towards the specific treatment of cancer - Hernández García, Yulán (2015)
Nowadays, cancer is one of the main causes of death worldwide, the cure of which makes it one of the most important targets of modern medicine. Conventional therapies are, either highly invasive (surgery) or little selective (chemo- and radiotherapy), which diminishes the effectiveness of these treatments leading to undesired secondary effects. Nanomaterials, due to its nano size, possess new special features that may provide several advantages for the diagnosis and treatment of this disease in all of its forms. These new systems, have great potential for leading to an early detection of cancer and the design of personalized therapies working only at target zones, improving the results obtained.